2021
DOI: 10.1016/j.ihj.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent coronary artery disease in Indian patients undergoing permanent pacemaker implantation (PPI) for symptomatic bradyarrhythmia

Abstract: Background The cause-effect of conduction disturbance in chronic lesion of coronary arteries is complicated. This study was designed to evaluate coexistent CAD in patients with symptomatic bradyarrhythmia to find common anatomic basis for conduction disturbances and its relationship to conventional coronary risk factors. Methods In this prospective observational study, 929 patients who admitted for symptomatic bradyarrhythmia requiring permanent pacemaker implantation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(25 reference statements)
0
2
0
Order By: Relevance
“… 28 Additionally, hypertension and hyperglycemia are well-established risk factors for adverse cardiovascular events. 29 31 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Additionally, hypertension and hyperglycemia are well-established risk factors for adverse cardiovascular events. 29 31 …”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Brueck et al, a direct causal link between the requirement for a pacemaker and CAD could not be definitively established based on the study results [ 15 ]. In the study by Vyas et al, obstructive CAD was detected in one-third of patients who underwent permanent pacemaker implantation [ 16 ]. It was observed that factors such as age equal to or greater than 50 years, male gender, diabetes, and hypertension showed a significant correlation with the presence of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…But these differences in the incidence of CAD in patients with bradyarrhythmia can be attributed to the baseline difference in the characteristics of the population in the two studies. Presence of multiple cardiovascular risk factors in the patient with bradyarrhythmia correlated better with the presence of a CAD [ 15 ]. Our patient who had a bradyarrhythmia underwent a coronary angiogram given the multiple cardiovascular high-risk factors he was having.…”
Section: Discussionmentioning
confidence: 99%